1997
DOI: 10.1007/s004250050132
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate ( 15 NO 3 ) limitation affects nitrogen partitioning between metabolic and storage sinks and nitrogen reserve accumulation in chicory ( Cichorium intybus L.)

Abstract: In chicory, we examined how NO 3 A supply aected NO 3 A uptake, N partitioning between shoot and root and N accumulation in the tuberized root throughout the vegetative period. Plants were grown at two NO 3 A concentrations: 0.6 and 3 mM. We used 15 N-labelling/ chase experiments for the quanti®cation of N¯uxes between shoot and root and for determining whether N stored in the tuberized root originates from N remobilized from the shoot or from recently absorbed NO 3A . The rate of 15 NO 3 A uptake was decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
6
16
0
Order By: Relevance
“…The high values of fructan contents observed in N-limited plants (figure 4) are consistent with other studies that showed an inverse relationship between fructan content and nitrogen concentration (Améziane et al 1997, Wang & Tilberg 1996, McGrath et al 1997, Van den Ende et al 1999. However, the fructan yield after 180 days was lower in plants transferred to N-limited solution due to their lower rhizophore biomass (figure 3), as previously reported for plants of V. herbacea cultivated exclusively under N-sufficient or N-limited conditions during one year (Cuzzuol et al 2005b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high values of fructan contents observed in N-limited plants (figure 4) are consistent with other studies that showed an inverse relationship between fructan content and nitrogen concentration (Améziane et al 1997, Wang & Tilberg 1996, McGrath et al 1997, Van den Ende et al 1999. However, the fructan yield after 180 days was lower in plants transferred to N-limited solution due to their lower rhizophore biomass (figure 3), as previously reported for plants of V. herbacea cultivated exclusively under N-sufficient or N-limited conditions during one year (Cuzzuol et al 2005b).…”
Section: Discussionsupporting
confidence: 91%
“…The reduction of cell division and cell expansion, leaf production and photosynthesis are evident effects in response to nitrogen deficiency . In some species of Asteraceae and Poaceae, for example, nitrogen restriction increased the contents of fructan-type carbohydrates (Wang & Tilberg 1996, Améziane et al 1997, Van den Ende et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Negligible differences between the genotypes for total protein accumulation and remobilization were observed despite important differences in total N and total amino acid accumulation. These results are in agreement with those of Améziane et al (1997) and RichardMolard et al (1999), who showed, in C. intybus L. cv. Bea, that neither protein accumulation in tuberized roots at the end of the vegetative phase nor protein mobilization during the forcing process or flowering in natural conditions were significantly affected by nitrogen fertilization levels.…”
Section: Article In Presssupporting
confidence: 95%
“…These results confirmed that the efflux of nitrogenous compounds from the leaf was controlled by the sink activity of the pods. This is similar to the situation in chicory, where the storage organ (tuberised root) was found to be the strongest sink for newly absorbed N (Ameziane et al 1997).…”
Section: Discussionsupporting
confidence: 81%